2006
DOI: 10.1152/ajpendo.00188.2006
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic glucose production is more sensitive to insulin-mediated inhibition than hepatic VLDL-triglyceride production

Abstract: Insulin is an important inhibitor of both hepatic glucose output and hepatic VLDL-triglyceride (VLDL-TG) production. We investigated whether both processes are equally sensitive to insulin-mediated inhibition. To test this, we used euglycemic clamp studies with four increasing plasma concentrations of insulin in wild-type C57Bl/6 mice. By extrapolation, we estimated that half-maximal inhibition of hepatic glucose output and hepatic VLDL-TG production by insulin were obtained at plasma insulin levels of approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Previous reports have shown effects of LXR activation on glucose metabolism in diabetic rodents (23)(24)(25). In the present study, we tested the effect of T0901317 on insulin-mediated changes in VLDL parameters.…”
Section: Effect Of T0901317 On Insulin Sensitivity Of Glucose Metabolismmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous reports have shown effects of LXR activation on glucose metabolism in diabetic rodents (23)(24)(25). In the present study, we tested the effect of T0901317 on insulin-mediated changes in VLDL parameters.…”
Section: Effect Of T0901317 On Insulin Sensitivity Of Glucose Metabolismmentioning
confidence: 94%
“…In normal mice, acute insulin infusion reduces VLDL-TG production rate (24), albeit more insulin is needed to suppress VLDL secretion than hepatic glucose production (25). Studies performed in vitro have shown that insulin is able to inhibit VLDL release via acceleration of apoB degradation (26), and as a result, insulin reduces the number of VLDL particles secreted.…”
mentioning
confidence: 99%
“…It is known that hepatic VLDL production depends on substrate availability, which is sensitive to insulin inhibition (7,(42)(43)(44). Such an inhibitory effect has been viewed as an acute mechanism to prime liver for rapid adaptation to metabolic shift from fasting to fed states.…”
Section: Figure 10mentioning
confidence: 99%
“…While the pathophysiology of hypertriglyceridemia is poorly understood, its close association with visceral adiposity and type 2 diabetes implicates insulin resistance as a causative factor for hypertriglyceridemia (3)(4)(5). VLDL is assembled and produced in the liver, which depends on substrate availability and is sensitive to insulin inhibition (6,7). In visceral obesity and type 2 diabetes, aberrant insulin action in coalition with increased influx of FFAs into liver promotes excessive VLDL-TG production, contributing to the pathogenesis of hypertriglyceridemia (3,4,8).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperinsulinemic euglycemic clamps were performed as described before [17][18][19][20][21], with minor modifications. Clamp experiments were performed after an overnight fast and under anesthesia by intraperitoneal injection with a combination of Acepromazin (0.5 mg/kg, Sanofi Santé Nutrition Animale, Libourne Cedex, France), Midazolam (0.25 mg/kg, Roche, Mijdrecht, The Netherlands) and Fentanyl (0.025 mg/kg, Janssen-Cilag, Tilburg, The Netherlands).…”
Section: Hyperinsulinemic Euglycemic Clampmentioning
confidence: 99%